PERANAN STICKER CUTTER DAN KOMPUTER DALAM PENINGKATAN KUALITAS SENI UKIR DAN CAT BOTOL KACA BEKAS DI KETAWANG GEDE MALANG - Supriyanto Supriyanto (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2015)
The purpose of this activity is intended to find solutions to improve the quality, quantity and enhance the competitiveness of craftsmen bottle (glass) ornamental. The method used is by observation to the field, interviews with stakeholders and training / pen beneficiaries. By using more modern equipment that sticker cutter and the computer can speed up and simplify the design of products with the result that much better quality. Because the place is only a business partner production house or yard is certainly very troubled by hot weather / rain which could stop the production process, therefore it should also be made a production process that is protected from heat / rain. The impact is going to accommodate more scavengers (the local community), the decline in unemployment and poverty, the reduction of social inequalities and craftsmen bottle (glass) can be more ornamental exist. The availability of jobs will affect the creation of a more harmonious relationship between the community and the creation of security and peace.